The Influence of Social Media Marketing Activities, Brand Awareness, Brand Image, Against Purchase Intention - Ridho Ramadhani Irdasyah; Renny Risqiani; Farah Margaretha (Jurnal Economic Resource, 2022)
This study aims to analyze the relationship between social media marketing activities used by several airlines and the dimensions of social media marketing activities, namely entertainment, customization, interaction, trendiness, e-word of mouth on brand awareness, and brand image to seek influence on purchase intention. This study used Survey Research on all airline service passengers in several Indonesian airlines, which was distributed to 161 respondents using a purposive sampling technique. Data testing methods are instrument tests with validity and reliability tests using SmartPLS software 3. Data analysis methods use Structural Equation Model (SEM) using SmartPLS software 3. The results reveal social media marketing activities' positive and significant impact on brand awareness and image. It was found that the dimensions of social media marketing activities, namely entertainment, customization, interaction, trendiness, and e-word of mouth, significantly had a positive effect on brand awareness and brand image, and brand awareness had a positive impact on brand image, while brand awareness did not influence purchase intention and brand image has a significant effect on purchase intention. This research has several theoretical and practical implications that can benefit managers, especially airlines, in their marketing to use various activities on social media such as Instagram, Twitter, Facebook, Youtube, and Tiktok.